HUBUNGAN INDEKS MASSA TUBUH (IMT) DENGAN KEKUATAN OTOT EKSTREMITAS INFERIOR PADA LANJUT USIA - Karisma (2021)
Background: As increasing age, many of elderly tend to reduce their activities due to chages and decreases in various function in the body. It will increase the prevalence of body weight that can reduce muscle strength of lower extremity. In fact, the muscle strength of the lower extremity will decrease by increasing the age and it can also get worse if the load is sustained too excessive. Objective: To determine the correlation BMI to muscle strength of lower extremity in elderly. Method: The study design is cross sectional study, with samples of 48 elderly people recorded at Yayasan Kalimatunsawa Indonesia, Bekasi. Measuring Instrument: BMI uses weight scales and stature meters and muscle strength of lower extremity with chair to stand test. Result data: In spearman hypothesis test muscle strength of lower extremity data obtained sig value. (2-tailed) is p = 0.690 where p > 0.05. Conclusion: There is no correlation between BMI and muscle strength of lower extremity in elderly. Keywords: BMI, muscle strength of lower extremity, elderly